Enhancing employee performance through job involvement, support, and competency in Indonesia.: Meningkatkan kinerja karyawan melalui keterlibatan, dukungan, dan kompetensi kerja di Indonesia - Rahmat, Renaldi; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of job involvement, perceived organizational support, and competency on job satisfaction and employee performance among 165 employees of PT. Harapan Sejahtera Karya Utama. Using questionnaires and path analysis with SPSS version 24, the research found that job involvement, organizational support, and competency positively affect employee performance directly and indirectly through job satisfaction. The study suggests organizations enhance job involvement, provide better supervisor support, offer training to improve competencies, and regularly evaluate salaries and reward systems to boost job satisfaction and performance. Highligt: Direct Impact: Job involvement, support, and competency enhance employee performance. Mediating Role: Job satisfaction mediates the factors' effects on performance. Strategies: Improve support, training, and evaluations to boost satisfaction and performance. Keyword: Job involvement, Organizational support, Competency, Job satisfaction, Employee performance